Cognitive Revised Bloom's Taxonomy Analysis in RPP PAI Documents in Senior High Schools (SMA) - Wildani Firdaus; Khozin (Penerbit Hellow Pustaka, 2024)
. In 1956 Benjamin S. Bloom formulated the concept of Bloom's Taxonomy, which became known as Bloom's Taxonomy along with the evolution of educational theory. Anderson and Krathwohl then revised Bloom's Taxonomy, describing two main dimensions, namely cognitive processes and levels of knowledge. In the learning context, especially in Islamic Religious Education subjects in Senior High Schools (SMA), an essential first step is the preparation of effective learning tools, including quality learning implementation planning (RPP) based on the 2013 curriculum, with a focus on core competencies. and basic competencies. Analysis of the distribution of cognitive levels in the RPP documents for Core Competencies (KI)-3, KI-4, Basic Competencies (KD)-3, and KD-4 shows that the levels of understanding (C2), application (C3), and analysis (C4) included in the learning process. Therefore, in the context of Islamic Religious Education, these subjects have achieved higher order thinking skills (HOTS).